If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (X + -2)(X + 1) + -4 = 0 Reorder the terms: (-2 + X)(X + 1) + -4 = 0 Reorder the terms: (-2 + X)(1 + X) + -4 = 0 Multiply (-2 + X) * (1 + X) (-2(1 + X) + X(1 + X)) + -4 = 0 ((1 * -2 + X * -2) + X(1 + X)) + -4 = 0 ((-2 + -2X) + X(1 + X)) + -4 = 0 (-2 + -2X + (1 * X + X * X)) + -4 = 0 (-2 + -2X + (1X + X2)) + -4 = 0 Combine like terms: -2X + 1X = -1X (-2 + -1X + X2) + -4 = 0 Reorder the terms: -2 + -4 + -1X + X2 = 0 Combine like terms: -2 + -4 = -6 -6 + -1X + X2 = 0 Solving -6 + -1X + X2 = 0 Solving for variable 'X'. Factor a trinomial. (-2 + -1X)(3 + -1X) = 0Subproblem 1
Set the factor '(-2 + -1X)' equal to zero and attempt to solve: Simplifying -2 + -1X = 0 Solving -2 + -1X = 0 Move all terms containing X to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1X = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -1X = 0 + 2 -1X = 0 + 2 Combine like terms: 0 + 2 = 2 -1X = 2 Divide each side by '-1'. X = -2 Simplifying X = -2Subproblem 2
Set the factor '(3 + -1X)' equal to zero and attempt to solve: Simplifying 3 + -1X = 0 Solving 3 + -1X = 0 Move all terms containing X to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1X = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1X = 0 + -3 -1X = 0 + -3 Combine like terms: 0 + -3 = -3 -1X = -3 Divide each side by '-1'. X = 3 Simplifying X = 3Solution
X = {-2, 3}
| 8x-10y=30 | | 4x-7=-2x+9 | | -3=-31+16.666 | | 0.10(m-100)+15+20=0.05m+40 | | 7t=6 | | 2x-19+3x+6+2x-10=180 | | 17k^2+119k=0 | | 9a-4=14 | | 4x=5y+6 | | A/6=-18 | | -3+9=-21 | | 2a+x=7 | | 3x+(-15+3x)=21 | | 8x-52=x | | 11x-9=8x+6 | | 9g^2+g=0 | | -7/3(y-12)-1/9y | | C-7.2=12 | | 3x^2+36x-8=0 | | 3x^2=19x+14 | | 13=-2+c | | y=ln(x^4+e^2x) | | 4*sin*2x-1=-5 | | -4b^2+81=0 | | 3(20+h)=1 | | f(x)=ln(x^4+e^2x) | | -24=-10a | | p=2m+n | | 2x-(-x+5)=6+(x+1) | | 11=h+3 | | 43o+8+6o=-90 | | 2(50-x)=40 |